2022
DOI: 10.1186/s12884-022-04811-y
|View full text |Cite
|
Sign up to set email alerts
|

The mediation role of psychological capital between family relationship and antenatal depressive symptoms among women with advanced maternal age: a cross sectional study

Abstract: Background Due to changes in family policy in China, pregnancy at advanced age (30 years old or above) is prevalent. Advanced maternal age is known to be related to a variety of negative health outcomes, including antenatal depression. Family relationship quality might be an important factor for antenatal depressive symptoms among Chinese women with advanced maternal age. However, the underlying mechanisms in which family relationship quality can affect antenatal depressive symptoms among this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
(61 reference statements)
0
3
1
Order By: Relevance
“…The association of these variables (depression, sleep quality, and body image disturbance) with various sociodemographic factors was not found to be significant in our study, indicating that these concerns are not restricted to a specific age group or population subset but rather warrant routine screening among all pregnant patients. Although the literature notes that depression [ 28 ], body image disturbances [ 25 ], and sleep problems [ 29 ] may be associated with age, we did not observe this in our study. Although advanced maternal age may be associated with higher levels of depression, it can also be hypothesized that women with earlier pregnancies are worried about the impact that childbirth can have on their lives and careers, thus leading to a nonsignificant difference in levels of depression noted between the two groups.…”
Section: Discussioncontrasting
confidence: 92%
“…The association of these variables (depression, sleep quality, and body image disturbance) with various sociodemographic factors was not found to be significant in our study, indicating that these concerns are not restricted to a specific age group or population subset but rather warrant routine screening among all pregnant patients. Although the literature notes that depression [ 28 ], body image disturbances [ 25 ], and sleep problems [ 29 ] may be associated with age, we did not observe this in our study. Although advanced maternal age may be associated with higher levels of depression, it can also be hypothesized that women with earlier pregnancies are worried about the impact that childbirth can have on their lives and careers, thus leading to a nonsignificant difference in levels of depression noted between the two groups.…”
Section: Discussioncontrasting
confidence: 92%
“…The results of this study extend the knowledge of previous research on psychological capital in the family context, which still needs to be improved. In the family context, psychological capital was found to minimize work-family conflict ( [39]; [40]; [40], positively related to family satisfaction [27] and family relationships ( [28]. That is, individuals who have high psychological capital tend to have high family well-being and satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the contribution of psychological capital to family resilience has yet to be well identified, although some studies have shown a positive relationship between family relationships and family satisfaction [27]; [28].…”
Section: Introductionmentioning
confidence: 99%
“…Plus, with the spread of the COVID-19 pandemic, the likelihood of suffering from MDD has increased significantly in different occupational groups ( Lokman and Bockting, 2022 ; Steen et al, 2022 ), such as COVID-19 survivors ( Mazza et al, 2022 ), healthcare workers ( Aoun et al, 2021 ; Moro et al, 2022 ), and self-quarantined people ( Nantaayi et al, 2022 ) around the world. Besides, MDD occurs not only as a primary disease alone, but also merges with other underlying diseases, including perimenopause ( Rudzinskas et al, 2021 ), puerperium ( Zeng et al, 2022 ), stroke ( Zhou et al, 2022 ), diabetes ( Bakker et al, 2022 ), Parkinson’s disease ( Xie et al, 2022 ), epilepsy ( Aimaier et al, 2022 ), hepatitis ( Gupta et al, 2020 ), gastritis ( Eustis et al, 2022 ), and brain cancer ( Nazli and Sevindik, 2022 ), as well as promotes the pathological development of the above diseases in turn. Thus, its occult pathogenesis features can easily lead to misdiagnosis ( Kostaras et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%